(untitled) (Bangladesh Journal of Zoology, 2012)
Chloroform extracts of fruit shell, leaf, root-bark, root-wood, seeds, stem-bark and stem-wood of Derris indica Bennet. were tested on the mosquito Culex quinquefasciatus Say larvae. The LC50 values of fruit shell, leaf, root-bark, root-wood, seed, stem-bark and stem-wood were 30762.54, 60922.83, 70070.31, 3867.32, 361.89, 453810.10 and 225860.20 ppm, respectively for 30 minutes of exposure; 220.60, 141.56, 59.54, 36.95, 21.52, 229.92 and 82.84 ppm, respectively for 24 hours of exposure, and 49.97, 34.00, 26.26, 18.33, 8.64 , 68.88 and 30.15 ppm, respectively for 48 hours of exposure. The dose-mortality effects were in the order: seed > root-wood > root-bark > stem-wood > leaf > fruit shell > stem-bark. DOI: http://dx.doi.org/10.3329/bjz.v39i2.10568 Bangladesh J. Zool. 39(2): 137-145, 2011